A influência do ambiente institucional na execução de projetos complexos para acesso aos mercados da base da pirâmide: um estudo de caso de organizações brasileiras no setor de utilidades públicas - Battistuzzo, Flávio Jorge Freire D. Andrade (2015)
World population is increasing and shall reach 9 billion at the end of 2050. The demand for basic services like energy, water and sanitation will increase. In Brazil, these services used to be provided by State owned enterprises. Despite the changes occurred after the privatization, the influence of the State on how organizations are structured is still a major fact. The challenge for the utilities services organizations in Brazil is how to deal with this ever-changing institutional environment in order to fulfill its social objective in an operational and economic efficiency. The organizations will have to innovate in their strategies to access the base of the pyramid, as its peculiarities are different from the top of pyramid. These innovations will be implemented through projects, with all the characteristics of complexities like size, innovations and new technologies. Understand the complexities dimensions in the execution of these projects is fundamental for the effective implementation of these strategies. Based on a multiple qualitative case study, this research answers the question “How does the participation of the State in utilities services organizations impact the execution of complex projects created to serve the base of pyramid markets?” with a focus in the Brazilian utilities services organizations. This research is based on a multiple case study, with a qualitative and exploratory nature, using an inductive approach. In order to perform this research, two utilities service organizations were selected with a representativeness of the sector. Data were collect based on a semi-structured interviews with respondents involved in the project execution to access the base of pyramid. Those were transcribed and a software for content analysis used to support the analysis of the research objectives. As a result of the research, complexities dimensions for project execution were identified, as well as the State influence on these projects and the organizational strategies. This research contributes in practical terms to a better understanding of the variants of the institutional elements with an impact on the strategies of the utilities services organizations. It reveals the need for a better understanding and definition of specific business model to attack the huge market opportunities at the base of pyramid. The identified results may be used by organizations to establish specific strategies for the base of pyramid considering the quantitative impacts of these strategies in the economic, social and environmental dimensions. Limitations from this research are established and suggestions for future works are presented.